Unveiling research dynamics: a bibliometric analysis of rule of law and corruption studies - Mohamed Hassan Mudey; Dayah Abdi Kulmie; Abdullahi Umar (Cogent Social Sciences)
This study aims to analyze the evolving research landscape on the rule of law and corruption between 2010 and 2023 through a bibliometric analysis of 809 documents from the Scopus database. The methodology includes Perish or Publish for citation matrix, Excel and R-package for advanced bibliometric visualization and network mapping. The analysis identifies the annual scientific production on the rule of law and corruption from 2010 to 2023, which shows a consistent growth trend. The United States is dominant in research, followed by the United Kingdom. Resource Policy Journal has published most of the article. The University of South Africa is the most productive institution. The findings advance scholarly knowledge by providing a comprehensive overview of research developments, revealing global interest and emphasizing the importance of interdisciplinary approaches. The study recommends expanding data sources such as Web of Science, Google Scholar and Dimensions while extending the temporal scope to capture historical trends and deeper qualitative insights.